2022
DOI: 10.3389/fnut.2022.925450
|View full text |Cite
|
Sign up to set email alerts
|

The plasma proteome is favorably modified by a high protein diet but not by additional resistance training in older adults: A 17-week randomized controlled trial

Abstract: BackgroundThe age-related loss of muscle mass significantly contributes to the development of chronic diseases, loss of mobility and dependency on others, yet could be improved by an optimized lifestyle.ObjectiveThe goal of this randomized controlled trial was to compare the influence of a habitual diet (CON) with either a diet containing the recommended protein intake (RP) or a high protein intake (HP), both with and without strength training, on the plasma proteome in older adults.MethodsOne hundred and thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…The functions of many other proteins identified are not well established. CNDP1 is a dipeptidase, and one previous study reported higher CNDP1 in people on high protein diets [48], which would be consistent with our observation of lower CNDP1 in non-meat eaters (not statistically significant in vegans) who generally have lower protein intake. Several of the proteins identified such as ART3, GAS6, THY1 and EGFR are involved in a range of signalling pathways and progression of tumour tissues [49][50][51][52], while other proteins including LAYN and CDHR2 are believed to have roles in cell adhesion [53,54].…”
Section: Other Proteinssupporting
confidence: 93%
“…The functions of many other proteins identified are not well established. CNDP1 is a dipeptidase, and one previous study reported higher CNDP1 in people on high protein diets [48], which would be consistent with our observation of lower CNDP1 in non-meat eaters (not statistically significant in vegans) who generally have lower protein intake. Several of the proteins identified such as ART3, GAS6, THY1 and EGFR are involved in a range of signalling pathways and progression of tumour tissues [49][50][51][52], while other proteins including LAYN and CDHR2 are believed to have roles in cell adhesion [53,54].…”
Section: Other Proteinssupporting
confidence: 93%
“…LC-MS/MS analysis was performed using a Dionex Ultimate3000 nanoLC-system (Thermo Fisher Scientific) coupled to the timsTOF Pro mass spectrometer (Bruker) equipped with a captive spray ion source as described previously. ,, Briefly, dried peptide samples were reconstituted in 5 μL of 30% formic acid (FA) containing standard peptides and diluted with 40 μL of loading solvent (97.9% H 2 O, 2% acetonitrile (ACN), 0.05% trifluoroacetic acid). Thereof, 1 μL was injected for LC-MS/MS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…LC-MS/MS analysis was performed as described previously. 12,14,15 Briefly, Dried peptide samples were reconstituted by adding 5 µL of 30 % formic acid (FA) containing four synthetic standard peptides and subsequent dilution with 40 µL of loading solvent (97.9 % H2O, 2 % ACN, 0.05 % trifluoroacetic acid). Thereof, 1 µL was injected into the Dionex Ultimate3000 nanoLC-system (Thermo Fisher Scientific).…”
Section: Serum and Plasma Proteomicsmentioning
confidence: 99%